2006
DOI: 10.1038/sj.gt.3302737
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral delivery of human CDC5 promotes G2/M progression and cell division in neonatal ventricular cardiomyocytes

Abstract: Heart failure results from the cumulative death of cardiomyocytes, and the inability of remaining cells to regenerate. Efforts toward transcriptional reprogramming of cardiomyocytes by overexpressing E1A or E2F1 have been limited by the inability of cardiomyocytes to enter and complete mitosis. Human CDC5 (hCDC5), a component of the pre-mRNA splicing complex, has been shown to regulate G2/M transit in asynchronously dividing cells. We now show that co-infection of recombinant adenoviruses expressing E1A/E1B an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…[87] (Figure 1). Depletion of CDC5L causes dramatic mitotic arrest, chromosome 220 misalignments and sustained activation of spindle assembly checkpoint [85, [88][89][90]. The mechanism can be inferred from data showing that CDC5L modulates the pre-mRNA splicing 222 of a set of genes involved in mitosis [89].…”
Section: Phase 178mentioning
confidence: 99%
“…[87] (Figure 1). Depletion of CDC5L causes dramatic mitotic arrest, chromosome 220 misalignments and sustained activation of spindle assembly checkpoint [85, [88][89][90]. The mechanism can be inferred from data showing that CDC5L modulates the pre-mRNA splicing 222 of a set of genes involved in mitosis [89].…”
Section: Phase 178mentioning
confidence: 99%
“…153 We recently found that leptin deficiency or resistance results in increased cardiomyocyte apoptosis, as assessed by TUNEL staining and caspase-3 levels. 154 Aged ob/ob and db/db mice showed increased DNA damage compared with old WT mice.…”
Section: Apoptosismentioning
confidence: 99%
“…Increased levels of Cdk1/cyclin B1 or decreased Cdk1 phosphorylation at Tyr 15 at P7 induces cardiomyocyte proliferation and entry to mitosis ( 15 , 53 ). Therefore, the balance between Wee1 and Cdc25 to regulate Cdk1 phosphorylation is critical for cardiomyocyte mitosis ( 15 , 43 , 54 ). Our data support the idea that decreased expression of both Per1 and Per2 clock genes increases cardiomyocyte proliferation and mitosis entry through suppression of Wee1.…”
Section: Discussionmentioning
confidence: 99%
“…To test this, we checked the levels of Cdk1/ cyclin B1, a protein complex for mitosis entry whose activity is regulated by Wee1 via phosphorylation (Fig. 5A) (15,43). Both mutant hearts showed decreased levels of inactive phospho-Cdk1 (Tyr 15 ) and increased levels of active Cdk1 and cyclin B1 (Fig.…”
Section: Wee1 Kinase Is Suppressed In Sn-deficient and Per1/per2-dele...mentioning
confidence: 99%